Strengthening Thailand's Agricultural drought Resilience -Questionnaire and Dataset - Goodwin, Daniel; Holman, Ian P.; Sutcliffe, Chloe; Rey Vicario, Dolores (Cranfield University, 2021)
Records of interviews with farmers in the Ping Catchment, Thailand as part of the STAR project. Interviews were undertaken in January 2020. A copy of the questionnaire is also provided.
Keywords: Agriculture'; 'questionnaire survey'; 'Drought management'; 'Agricultural Land Management'